A Study on an Inter-Institutional Collaboration of Family, Community, and Buddhism for Thai Vulnerable Youth - Phattharachai Uthaphan; Radchaneeboon Neadpuckdee; Prasong Promsri; Prachan Chachikul; Surawut Saengmano (Journal of Educational Issues, 2024)
The purpose of the study was to investigate the effects of the inter-organizational collaboration of family, community, and Buddhism on vulnerable youth knowledge and behaviors. The samples were 302 vulnerable youths in Khon Kaen in Northern Thailand. They were selected by purposive sampling using the criteria of family incomes, marital status of parents, and neighborhood. The other group of samples consisted of 10 officials with the responsibility to take care of vulnerable youth in their area. The instruments included an inter-institutional collaboration plan, a teen pregnancy knowledge test, a social adaptation test, a drug knowledge test, and an interview form. The data were gathered in August 2021 when the samples took part in 5 projects under the inter-institutional collaboration plan involving family, community, and Buddhism. The data were analyzed using frequency, percentage, mean score, standard deviation, and t-test. The qualitative data were analyzed by content analysis. The results study illustrates how a planned collaboration between institutions concerned with human development led to the development of knowledge and positive behavioral changes among vulnerable youths.